South Asia : Politics, Religion and Society - Edited By Massarat Abid and Qalb-i-Abid (Lahore Pakistan Studty Center, 2008)
Papers presented at the International Conference on Perspectives on Religion, Politics and Society in South Asia, held at Lahore during 19-20 February 2007.
Include Notes and References
Keywords: South Asia -- South Asia -- Politics and Government